THE EFFECTS OF MATERNAL OBESITY ON MATERNAL AND NEONATAL OUTCOMES IN WOMEN WITH GESTATIONAL DIABETES - Faraj, Fatima Habeeb; Mahmood, Maryam Bakir; Muhammad, Huda Muheddin; Salih, Jamal Mahmood (Journal of Sulaimani Medical College, 2022)
Background Obesity and gestational diabetes mellitus (GDM) can interfere. Poorly controlled blood glucose can cause unfavourable maternal and neonatal outcomes. Objectives The study aims to know the effects of maternal obesity on maternal and neonatal outcomes in pregnant women with controlled GDM.. Patients and Methods A prospective observational study was performed on 90 pregnant women with GDM admitted to Sulaimani Maternity Teaching Hospital from January 2020 to January 2021. Maternal and gestational ages, residencies, gravidity, and parity were recorded. In addition, maternal body mass index, depending on Rcog guidelines for blood glucose targets, mode of delivery, and maternal and neonatal complications were noted. Also, neonatal complications were documented, including Apgar score and body weight. Results Maternal ages were 34.2±6.4 years, ranging from 21 to 45. Most of them (92.3%) resided inside Sulaimani. None of the maternal outcomes had a significant association with their body weight (P-value >0.05). One woman in the obese group had intrauterine fetal death. All neonatal consequences were significantly associated with maternal body weight (P-value <0.05). Conclusion The current study did not find significant associations between maternal body weights with maternal outcomes in women with controlled GDM. However, at the same time, maternal obesity has significantly increased neonatal complications.
Keywords: Maternal obesity; Gestational Diabetes; Maternal Outcomes; Neonatal outcomes